2016
DOI: 10.1186/s40561-016-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Videos in learning in higher education: assessing perceptions and attitudes of students at the University of Ghana

Abstract: Video is one of the most diversified and distinct virtual learning mediums that capture and present information and offer a sensory learning environment, which enables learners to understand more and retain information better. This study sought to assess the perceptions and attitudes of students at the University of Ghana towards the use of videos as a medium for teaching and learning. Qualitative data was collected using semi structured interviews. Participation was entirely voluntary and was conditional, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…This is probably related to the fact that students actively engaged in viewing the micro-lectures, and because the course structure gave them more time outside of class to process the information introduced in the micro-lectures. Students benefited from the micro-lectures they watched in relation to this course, which supports the claim that micro-lectures are a valid means of achieving desired learning goals (Boateng, Boateng, Awuah, Ansong, & Anderson, 2016). Moreover, online exercises provided a timely method of consolidating knowledge after watching the micro-lectures, which helped students better grasp what they had learned.…”
Section: Discussionsupporting
confidence: 71%
“…This is probably related to the fact that students actively engaged in viewing the micro-lectures, and because the course structure gave them more time outside of class to process the information introduced in the micro-lectures. Students benefited from the micro-lectures they watched in relation to this course, which supports the claim that micro-lectures are a valid means of achieving desired learning goals (Boateng, Boateng, Awuah, Ansong, & Anderson, 2016). Moreover, online exercises provided a timely method of consolidating knowledge after watching the micro-lectures, which helped students better grasp what they had learned.…”
Section: Discussionsupporting
confidence: 71%
“…At the international level, previous studies have shown that university students generally exhibit positive attitudes towards ICT [16,30]. Other researchers have found similar results but warned of the need to consider whether effective use is being made of the technology [31]. Positive attitudes have also been found towards social tools [32].…”
Section: University Students' Attitudes Towards Ictmentioning
confidence: 77%
“…Student perception of enhanced learning experiences has been described by multiple authors (Boateng et al, 2016;Danielson et al, 2013;Rose, 2009). The positive perceptions exemplified by students in the current study is in line with previous research on video technology as a supplemental learning tool.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and learning in higher education must meet the challenges of today's rapidly evolving educational environments. This can be accomplished by incorporating technologies that current students readily interact with and which facilitate flexibility in learning (Boateng, Boateng, Awuah, Ansong, & Anderson, 2016;Kelly, Lyng, McGrath, & Cannon, 2009). A flexible learning environment, which supports independent learning, may be a desirable component of a learning environment for the student in higher education.…”
Section: Introductionmentioning
confidence: 99%